Risk appetite and exchange rates - Tobias Adrian; Erkko Etula; Hyun-Song Shin (Federal Reserve Bank of New York, 2015)
We present evidence that the growth of U.S.-dollar-denominated banking sector liabilities forecasts appreciations of the U.S. dollar, both in-sample and out-of-sample, against a large set of foreign currencies. We provide a theoretical foundation for a funding liquidity channel in a global banking model where exchange rates fluctuate as a function of banks' balance sheet capacity. We estimate prices of risk using a cross-sectional asset pricing approach and show that the U.S. dollar funding liquidity forecasts exchange rates because of its association with time-varying risk premia. Our empirical evidence shows that this channel is separate from the more familiar "carry trade" channel. Although the financial crisis of 2007-09 induced a structural shift in our forecasting variables, when we control for this shift, the forecasting relationship is preserved.
Keywords: F30; F31; G12; G24; 330; asset pricing; financial intermediaries; exchange rates